On the presence of Alsodes coppingeri (Anura, Alsodidae) in Argentina, with comments on other southern Alsodes - Barrasso, Diego Andrés (2022)
The occurrence of Alsodes coppingeri is confirmed in Argentina for the first time, from Santa Cruz Province, close to the Lago del Desierto. Specimens of this species were identified according to external morphology and DNA sequences. These new records in Argentina are at the same latitude than the type locality (Puerto Río Frío, Chile) about 100 km eastwards in a straight-line, but at the opposite side of the Andes mountain range and the Southern Continental Ice Fields. Five localities from Chile (Caleta Tortel, Canal Michel, Laguna Caiquenes, Puerto Yungay, and Villa O’Higgins) are around 100 km north from our records, in a lower region of the Andes located between the Northern and Southern Continental Ice Fields. This region with discontinuous permanent ice sheet-cover may have acted as a corridor for amphibian species that are currently distributed on both sides of the Andes range.